A study of the curing kinetics of polyester resin from palm oil - Loh, Wee Keat (2014)
In the present work, curing kinetics of polyester resin from palm oil was studied. The main objective of this research was to cure the unsaturated polyester resin (UPR) with different composition of methyl ethyl ketone peroxide (MEKP) in the presence of cobalt napthenate or lead naphthenate as dryer, and analyse their curing kinetics. Besides, a comparison was drawn between cobalt napthenate and lead naphthenate in terms of drying time for the best composition of UPR and MEKP ratio. The findings suggest that the best composition of UPR/MEKP was 45 phr (parts per hundred gram of sample) UPR: 20 phr MEKP, with the shortest drying time (7 h), while cobalt naphthenate was found to be more suitable dryer that helped to accelerate the curing reaction. After that, the curing of 45 phr UPR: 30 phr styrene: 20 phi MEKP: 5 phr cobalt naphthenate was studied-by differential scanning calorimetry (DSC) at different heating rates such as 10, 15 and 20°C/min. Two exothermic peaks were found as confirmed by the DSC thermogram. A set of kinetic parameters such as activation energy, reaction rate, rate constant and reaction order for the first peak were calculated by using different equations and established methods. Result analyses revealed the activation energies as 44.21, 25.71 and 18.600/mol for heating rate of 10, 15 and 20°C/mm, respectively. Additionally, the order of reaction for each heating rate was obtained from the plotting of graph and stated as 2.0508 for 10°C/mm, 1.0933 for 15°C/min and 0.5197 for 20°C/min. Moreover, glass transition temperature of the UPR also analysed and found to be -5°C, which was quite low.